Ozone distribution over India - TIWARI, V. S. (MAUSAM, 1974)
Using Dobson ozone spectrophotometer data from a network of six stations in India, the spatial and temporal distribution of total ozone over the country and its vertical distribution in the atmosphere during 1964-1969 have been studied. The study confirms earlier observations and shows that over stations north of 25°N the seasonal increase in total ozone is caused by * fractional increase in all layers from the ground to 28 km, the main contribution coming from the layers between 10 and 24 km. Above 28 km the concentration changes roughly in accordance with photochemical production. In lower latitudes south of 25°N an increase in total ozone amount during the annual cycle is caused by a gradual increase in all the layers from the ground to 36 km, above which the variation is negligible.